Quantitative Estimation and Comparative Analysis of Polysaccharides and Proteins in Common Dietary Pulses - Y. Karthikeyan; P. Abinaya; P. Revathi (Kongunadu Research Journal, 2025)
Pulses are edible seeds from legume plants and are a rich source of polysaccharides and proteins. Estimating the polysaccharide and protein content in pulses provides valuable insights into their nutritional composition. Polysaccharides, primarily in the form of starch and dietary fiber, contribute to the energy content and functional properties of pulses. Proteins, as a major macronutrient in pulses, play a crucial role in human nutrition, particularly as a plant-based protein source.In the present study, there are four main pulses has been selected for the estimation of polysaccharides and proteins such as Vigna mungo (Black gram), Pisum sativum (Green peas), Trigonella foenum graecum (Fenugreek), and Cicer arietinum (Bengal gram) using standardized methods. The dried pulse seeds were powdered and extracted with water to obtain gum.Total polysaccharides were significantly higher in Trigonella foenum-graecum and Vigna mungo, while total protein content was highest in Trigonella foenum-graecum, followed by Cicer arietinum. In both analyses, Trigonella foenum-graecum showed the highest levels of estimated phytochemicals, indicating that it contains the highest amounts of bioactive primary metabolites (polysaccharides and proteins). This research report suggested that mung dal and chickpea may also offer significant health benefits. The study recommends including Trigonella foenum-graecum, followed by Vigna mungo and Cicer arietinum, in regular diet to obtain both medicinal and nutritional health benefits.